1999
DOI: 10.1038/22326
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of tuberculosis in mice by DNA vaccination

Abstract: Mycobacterium tuberculosis continues to kill about 3 million people every year, more than any other single infectious agent. This is attributed primarily to an inadequate immune response towards infecting bacteria, which suffer growth inhibition rather than death and subsequently multiply catastrophically. Although the bacillus Calmette-Guerin (BCG) vaccine is widely used, it has major limitations as a preventative measure. In addition, effective treatment requires that patients take large doses of antibacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
318
1
11

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(334 citation statements)
references
References 30 publications
4
318
1
11
Order By: Relevance
“…23 Interestingly, Lowrie et al recently reported that the vaccination of plasmid DNA expressing hsp65 after chemotherapy proved effective at preventing the reactivation of M. tuberculosis. 24,25 These results suggest that immunotherapy designed to boost the efficiency of the immune system in infected patients could be a valuable adjunct to antibacterial chemotherapy.…”
Section: Introductionmentioning
confidence: 96%
“…23 Interestingly, Lowrie et al recently reported that the vaccination of plasmid DNA expressing hsp65 after chemotherapy proved effective at preventing the reactivation of M. tuberculosis. 24,25 These results suggest that immunotherapy designed to boost the efficiency of the immune system in infected patients could be a valuable adjunct to antibacterial chemotherapy.…”
Section: Introductionmentioning
confidence: 96%
“…[14][15][16] For example, the vaccination of plasmid DNA expressing hsp65 after completion of chemotherapy was shown to be effective in preventing the reactivation of intravenously infected M. tuberculosis. 17 In addition, we recently demonstrated that Ag85A DNA vaccine, when simultaneously treated with chemotherapy, could be effective in preventing reactivation of aerogenically infected M. tuberculosis. 18 In contrast, Hsp60 or Ag85A DNA vaccines, which were administered after chemotherapy, had no effect.…”
mentioning
confidence: 99%
“…23,24 In therapeutic settings, HSP65 and Ag85A are the most extensively tested antigens, but their protective efficacies remain a subject of controversy. 21,22,25 Head-to-head comparison of potent TB antigens under a single experimental condition may be the ideal approach for identifying protective antigens, especially when infection models are diverse like TB. 26 In this study, we initially demonstrated that F-Mtb32 DNA vaccination provides superior protective immunity than the other six candidates, either as a prophylactic or therapeutic vaccine against M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%